The potential of reverse innovation to improve urban toilets - Tierney, Ross (Cranfield University, 2017)
The lack of desirable, waterless toilet options in urban environments around the world leads to major issues that will continue to get worse as population density increases. At the bottom of the economic pyramid, 2.3 billion people lack access to adequate sanitation accelerating the spread of disease through contaminated water and leading to the deaths of over a million children per year. At the top of the economic pyramid, the ubiquitous flushing toilet uses nine litres of water per flush, equating to the average person using 15,000 litres of water per year. As clean water becomes a scarcer resource, wasting and polluting water has to be avoided. Developing new water-saving, desirable toilets to provide a pleasant user experience will increase the likelihood of adoption of more sustainable options. Defecation is a basic human function but also a universal cause for embarrassment and disgust. As the repulsion is visceral and ‘hard-wired’ human behaviour, many of the same issues arise whether the user is in the poorest slum or a modern apartment building. Designing new products for low income countries that find a secondary market in a high income country is an approach called reverse innovation and has a proven record of producing disruptive innovations by working to strict requirements. This research discusses how reverse innovation has potential to address the challenges and issues associated with low-water sanitation to increase adoption of more sustainable technology. To achieve this, an understanding was gained of the user experience of different low-water toilets through literature review and an ethnographic study in Kumasi, Ghana. A new waterless toilet technology was then developed and tested, primarily targeting the residents of Kumasi before being tested with a secondary target market in the United Kingdom. There were a number of similarities across both target markets, confirming the importance of user experience. The technology was positively received and compatible with user behaviour in the secondary target market indicating the technology could be transferred and an example of reverse innovation. This research intends to encourage and inspire innovation in a sector that effects everyone in the world yet remains an ignored and embarrassing subject.
Keywords: Product development; sanitation; reverse innovation; design for developing countries; urban sustainability